2005
DOI: 10.1038/nn1471
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic modulation of limbic and cortical drive of nucleus accumbens in goal-directed behavior

Abstract: Goal-directed behavior is believed to involve interactions of prefrontal cortical and limbic inputs in the nucleus accumbens (NAcc), and their modulation by mesolimbic dopamine (DA) seems to be of primary importance in NAcc function. Using in vivo electrophysiological recordings simultaneously with DA system manipulation in rats, we show that tonic and phasic DA release selectively modulates hippocampal and prefrontal cortical inputs through D1 and D2 receptors, respectively. In addition, we also found that D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
457
6
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 531 publications
(505 citation statements)
references
References 34 publications
38
457
6
4
Order By: Relevance
“…Our finding concurs with the observation that the effect of L-DOPA stems from its ability to elevate DA in the striatum (Hornykiewicz, 1974;Carey et al, 1995) and suggests that at least some 'frontal-like' deficits in PD reflect disruption of frontal input to the striatum (Goto and Grace, 2005) or alternatively, striatal outflow to the PFC (Owen et al, 1998;Dagher et al, 2001). The present lack of cortical modulation of reversal-related activity apparently contradicts results from previous imaging studies in PD, which have revealed cortical changes (Cools et al, 2002b;Mattay et al, 2002;Lewis et al, 2003;Monchi et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our finding concurs with the observation that the effect of L-DOPA stems from its ability to elevate DA in the striatum (Hornykiewicz, 1974;Carey et al, 1995) and suggests that at least some 'frontal-like' deficits in PD reflect disruption of frontal input to the striatum (Goto and Grace, 2005) or alternatively, striatal outflow to the PFC (Owen et al, 1998;Dagher et al, 2001). The present lack of cortical modulation of reversal-related activity apparently contradicts results from previous imaging studies in PD, which have revealed cortical changes (Cools et al, 2002b;Mattay et al, 2002;Lewis et al, 2003;Monchi et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…In the OFF state, patients demonstrated NAc activity during the final reversal errors that preceded behavioral adaptation. L-DOPA disrupted this NAc activity, consistent with work with experimental animals (Goto and Grace, 2005). These findings support the suggestion that DA interacts with the NAc to bias reversal learning and demonstrate the utility of early PD, with differentially depleted neural systems, as a model for exploring the role of DA in normal cognitive function.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…GPe ϭ external segment of the globus pallidus. Goto & Grace, 2005). Thus, smaller decreases in DA firing may be sufficient to functionally affect D 2 receptors, which drives no-go learning in our model.…”
Section: Ofcmentioning
confidence: 78%